Mechanism Design for Robotics - Ceccarelli, Marco; Gasparetto, Alessandro (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
MEDER 2018, the IFToMM International Symposium on Mechanism Design for Robotics, was the fourth event in a series that was started in 2010 as a specific conference activity on mechanisms for robots. The aim of the MEDER Symposium is to bring researchers, industry professionals, and students together from a broad range of disciplines dealing with mechanisms for robots, in an intimate, collegial, and stimulating environment. In the 2018 MEDER event, we received significant attention regarding this initiative, as can be seen by the fact that the Proceedings contain contributions by authors from all around the world.The Proceedings of the MEDER 2018 Symposium have been published within the Springer book series on MMS, and the book contains 52 papers that have been selected after review for oral presentation. These papers cover several aspects of the wide field of robotics dealing with mechanism aspects in theory, design, numerical evaluations, and applications.This Special Issue of Robotics (https://www.mdpi.com/journal/robotics/special_issues/MDR) has been obtained as a result of a second review process and selection, but all the papers that have been accepted for MEDER 2018 are of very good quality with interesting contents that are suitable for journal publication, and the selection process has been difficult.